Isolasi dan Identifikasi Bakteri dari Tinja Orangutan Penderita Gangguan Gastrointestinal (BACTERIAL ISOLATION AND IDENTIFICATION IN FAECES OF ORANGUTAN WITH GASTROINTESTINAL DISTURBANCE) - Wibowo, Michael Haryadi; Rosetyadewi, Antasiswa Windraningtyas; Wijayanti, Agustina Dwi; Airin, Claudia Mona (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Orangutans are among protected animals by the law. One of orangutans’ main health problems isgastrointestinal disease due to bacterial infection. Microbiological data of causative agent of illness inorangutan still not much reported scientifically. This research aim was to identify causative agent ofbacterial infection on gastrointestinal disorder in orangutan isolated from stool samples. The sampleswere collected from Yayasan Konservasi Alam Yogyakarta and Borneo Orangutan Survival, Semboja,Kalimantan Timur. Fresh fecal samples were collected using sterile swab and put them into a steriletransport media. To achieve pure cultures, bacterial isolation was performed by using plate streaking onselective media. Gram stain was done to confirm the cell uniformity and morphology. Bacterialidentification was performed according to Bergey’s Manual Determinative Bacteriology on some biochemicalcharacters to determine the isolated bacteria. The result showed that three bacteria were identified fromstool samples orangutan from Yayasan Konservasi Alam Yogyakarta, i.e.: Citrobacter amalonaticus,Providensia rustigianii, and Proteus mirabilis. Meanwhile, three bacteria, which were Klebsiella planticola,Enterobanter agglomerans and Escherichia coli, were also identified in samples taken from Borneo orangutan.
Keywords: enteric bacteria; pure culture; biochemical reaction; orangutan